Correction: The influence of successor's implicit power and explicit power on dual innovation---The mediating effect of board dissent. - Wang Feifei; Wu Jiong; Marcello Russo; Luyang Gao (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0275603.].